Dylematy kwestii agrarnej w panoramie dziejów - Czyżewski, Andrzej; Matuszczak, Anna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The article presents the universal dilemmas of the agrarian question. The outset there has been historical references relating to the management of land, reaching antiquity. In turn pointed to attempts to define and solve the agrarian question, with particular emphasis on the views of agrarists. At the same time contains the parallel reference to the present, the substitution money by land, food security, income disparity issues and seek alternative sources of income. Historical dilemmas were brought to the ground today, by showing their timelessness. You can now conclude that the agrarian question is lasting, and relatively recent problem of conscious sustainability of agriculture, seen as an organic whole, which itself is not followed and will not reconcile the interests of economic, social and environmental impacts.